(untitled) (PerCursos, 2022)
Atalaia Beach, located in the municipality of Salinópolis, northeast of the state of Pará, is a place where abundant paleontological records occur. However, despite of having been studied for decades, this records is not formally recognized by the heritage protection institutions, which hinders conservation measures aimed at the fossils that outcrop on the beach. In this context, the present study aimed to quantitatively evaluate the geoheritage values of Atalaia Beach. For this, we used the GEOSSIT online platform, which is the Registration and Quantification System of Geosites and Geodiversity Sites in Brazil. It was obtained the values of 305 for the risk of degradation, 170 for scientific value, 300 for educational value and 275 for the tourist value. The paleontological site was classified as a Geodiversity Site, having high educational and tourist potential. The quantification of Atalaia Beach’s paleontological records is one of the first steps towards its recognition, thus ensuring that various geoconservation measures can be applied, preserving the geological heritage of the Eastern Amazon.